Essential functions of the CNOT7/8 catalytic subunits of the CCR4-NOT complex in mRNA regulation and cell viability. Issue 3 (3rd March 2020) - Mostafa, Dina; Takahashi, Akinori; Yanagiya, Akiko; Yamaguchi, Tomokazu; Abe, Takaya; Kureha, Taku; Kuba, Keiji; Kanegae, Yumi; Furuta, Yasuhide; Yamamoto, Tadashi; Suzuki, Toru
ABSTRACT: Shortening of mRNA poly(A) tails (deadenylation) to trigger their decay is mediated mainly by the CCR4-NOT deadenylase complex. While four catalytic subunits (CNOT6, 6L 7, and 8) have been identified in the mammalian CCR4-NOT complex, their individual biological roles are not fully understood. In this study, we addressed the contribution of CNOT7/8 to viability of primary mouse embryonic fibroblasts (MEFs). We found that MEFs lacking CNOT7/8 expression [ Cnot7/8 -double knockout (dKO) MEFs] undergo cell death, whereas MEFs lacking CNOT6/6L expression ( Cnot6/6l -dKO MEFs) remain viable. Co-immunoprecipitation analyses showed that CNOT6/6L are also absent from the CCR4-NOT complex in Cnot7/8 -dKO MEFs. In contrast, either CNOT7 or CNOT8 still interacts with other subunits in the CCR4-NOT complex in Cnot6/6l -dKO MEFs. Exogenous expression of a CNOT7 mutant lacking catalytic activity in Cnot7/8 -dKO MEFs cannot recover cell viability, even though CNOT6/6L exists to some extent in the CCR4-NOT complex, confirming that CNOT7/8 is essential for viability. Bulk poly(A) tail analysis revealed that mRNAs with longer poly(A) tails are more numerous in Cnot7/8 -dKO MEFs than in Cnot6/6l -dKO MEFs. Consistent with elongated poly(A) tails, more mRNAs are upregulated and stabilized in Cnot7/8 -dKO MEFs than in Cnot6/6l -dKO MEFs. Importantly, Cnot6/6l -dKO mice are viable and grow normally to adulthood. Taken together, the CNOT7/8 catalytic subunits are essential for deadenylation, which is necessary to maintain cell viability, whereas CNOT6/6L are not.